Development of An Instrument to Measure Self Endurance - Dewi, Ni Made Sulistrisiana; Dharsana, I Ketut; Suarni, Ni Ketut (Bisma The Journal of Counseling, 2020)
The purpose of this research development is to determine the value of the validity of the instrument as well as to find out the reliability value of the instrument of self endurance questionnaire. This research was included research and development (R&D) with a four-D (4D) model which is a research method for producing or developing a particular product. The 4D research model consists of four steps: 1) defining (collecting references or references used to collect research products), 2) design (collecting product self-endurance questionnaire instruments), 3) developing (developing products through expert judgement research or experts), and 4) dessiminate (ie the distribution of research products). The data analysis used in this study was to know the validity of the Lawshe CVR and CVI tests as well as the reliability test of the questionnaire with the Alpha Cronbach coefficient. Testing the validation of the instrument was carried out by 5 experts consisting of 3 lecturers of the Undiksha Counseling Guidance Postgraduate Program and 2 BK teachers. The results of the CVR calculation of the self-endurance instrument with 40 approved items have obtained results of more than 0 (> 0), which means 40 items are declared valid. Furthermore, an analysis of CVI data with a result of 0.98 or CVI of more than 0, then the questionnaire instrument was declared valid. After calculating the reliability value (r11) the self-endurance instrument is 0.918 with the very high reliability category.